2013
DOI: 10.1002/eji.201343617
|View full text |Cite
|
Sign up to set email alerts
|

Activation of human basophils by combined toll‐like receptor‐ and FRI‐triggering can promote Th2 skewing of naive T helper cells

Abstract: Additional supporting information may be found in the online version of this article at the publisher's web-site IntroductionBasophils are circulating granulocytes that can migrate to tissues when inflammation or other triggers are present locally. Activation of basophils through crosslinking of FcεRI via antigen-specific IgE causes the release of granule contents (histamine, proteoglycans), lipid-derived mediators (leukotrienes), and cytokines. Due to their potent activation via IgE-bound antigens and their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…This process causes a vicious cycle wherein each disease flare can initiate further autoantibody production and tissue injury (107)(108)(109). Furthermore, combined TLR-and Fc receptor-mediated activation of myeloid cells often leads to an enhanced inflammatory response that is thought to contribute to the chronicity of inflammation (51,94,110,111). Therefore, those self-antigens that can most potently activate B cells because they are TLR ligands may also potently enhance pathogenic inflammatory responses (Figure 3).…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…This process causes a vicious cycle wherein each disease flare can initiate further autoantibody production and tissue injury (107)(108)(109). Furthermore, combined TLR-and Fc receptor-mediated activation of myeloid cells often leads to an enhanced inflammatory response that is thought to contribute to the chronicity of inflammation (51,94,110,111). Therefore, those self-antigens that can most potently activate B cells because they are TLR ligands may also potently enhance pathogenic inflammatory responses (Figure 3).…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…Even though the role of the sialylated fraction of IVIG or basophils in the immunomodulatory effects of IVIG therapy has recently been challenged [9], another study using an experimental model of IgE-mediated chronic allergic inflammation, showed that mouse basophils, through IL-4, drive the differentiation of monocytes into anti-inflammatory macrophages, thereby regulating chronic allergic skin inflammation in vivo [10]. Human basophils, which can significantly differ from their mouse counterparts [1,3,11], have been known for a long time to produce , and have been recently shown to induce Th2 skewing of naïve helper T cells in vitro [13,14]. On the other hand, the function as antigen presenting cells, still debated in mice, has been ruled-out for human basophils by several groups [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Human basophils, which can significantly differ from their mouse counterparts [1,3,11], have been known for a long time to produce IL-4 [12], and have been recently shown to induce Th2 skewing of naïve helper T cells in vitro [13,14]. On the other hand, the function as antigen presenting cells, still debated in mice, has been ruled-out for human basophils by several groups [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…13 Therefore, we stimulated basophils with lipopolysaccharide from E. coli (LPS, TLR4 agonist), FSL-1 (Pam2CGDPKHPKSF, TLR2/6 agonist), or CpG ODN (TLR9 agonist). Furthermore, we also used papain as a model allergen in our experiments, and this cysteine protease allergen can directly activate basophils and promote murine basophil-mediated Th2 responses.…”
Section: -12mentioning
confidence: 99%
“…Furthermore, we also used papain as a model allergen in our experiments, and this cysteine protease allergen can directly activate basophils and promote murine basophil-mediated Th2 responses. 4 Since, IgEbound antigens/allergens provide the most-potent activation signal for basophils, 13,14 this stimulation condition was mimicked by crosslinking of surface FcεRI-bound IgE by using anti-IgE antibodies (See Online Supplementary Methods).…”
Section: -12mentioning
confidence: 99%